2017
DOI: 10.1177/1479972317702140
|View full text |Cite
|
Sign up to set email alerts
|

Presentation, management and mortality after a first MI in people with and without asthma: A study using UK MINAP data

Abstract: Asthma has been associated with a higher incidence of myocardial infarction (MI), higher prevalence of MI risk factors and higher burden of cardiovascular diseases. However, detailed associations between the presentation and initial management at the time of MI and post-MI outcomes in people with asthma compared to the general population have not been studied. A total of 300,161 people were identified with a first MI over the period 2003–2013 in the Myocardial Ischaemia National Audit Project database, of whom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Observational studies and limited controlled data have shown no difference in exacerbations or hospital admissions among asthmatic patients using cardio‐selective beta 1 ‐blockers and we have been unable to find any published reports of cardio‐selective beta 1 ‐blockers precipitating fatal asthma 10–13 . Despite this, cardio‐selective beta 1 ‐blockers remain relatively contraindicated in asthma and clinicians are reluctant to use them 14–19 …”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Observational studies and limited controlled data have shown no difference in exacerbations or hospital admissions among asthmatic patients using cardio‐selective beta 1 ‐blockers and we have been unable to find any published reports of cardio‐selective beta 1 ‐blockers precipitating fatal asthma 10–13 . Despite this, cardio‐selective beta 1 ‐blockers remain relatively contraindicated in asthma and clinicians are reluctant to use them 14–19 …”
Section: Introductionmentioning
confidence: 86%
“…[10][11][12][13] Despite this, cardioselective beta 1 -blockers remain relatively contraindicated in asthma and clinicians are reluctant to use them. [14][15][16][17][18][19] People with asthma are more likely to develop heart disease. 20,21 With an ageing population, many people with asthma have cardiac comorbidities.…”
Section: Introductionmentioning
confidence: 99%
“…P values were calculated from Z values obtained from the difference between the main effect and 95% confidence intervals at each time point between the two countries (see supplementary material). Missing covariates were imputed using the approach suggested for MINAP, imputing unrecorded as 'absent' or 'no' 21 .…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Coronary artery disease (CAD) is a leading cause of death worldwide, and despite lowering age-specific mortality rates in affluent countries, an aging population keeps the absolute numbers rising [ 3 ]. It has the following subtypes: stable ischemic CAD and acute coronary syndrome (ACS).…”
Section: Introductionmentioning
confidence: 99%